PENGENDALIAN KUALITAS PRODUK PLASTIK MENGGUNAKAN SIX SIGMA GUNA MENINGKATKAN DAYA SAING - Basjir, Mochammad; Suhartini, Suhartini; Robbi, Nur (Journal of Research and Technology, 2023)
One of the products produced by PT. XYZ is in the form of a white plastic spoon in the production process, and problems are often found in the form of products having defects that significantly affect the quality, management system, and expenses of the company. To overcome this, an analysis was carried out using the Six Sigma method, and from the calculation results obtained a sigma value of 3.9 with a defect value of 10531 for a million production. From the results of the analysis carried out to push the company towards zero defects by seeking improvements to machine and human factors as the main factors for product defect problems, some of the recommendations for improvements given are to carry out maintenance on the machines and tools that exist in the company, to rearrange the machines damaged by changing parts so as not to hinder the ongoing production flow, supervising worker operators using Production Operations Standards (SOP), conducting a worker appraisal system according to applicable regulations so that workers are motivated to perform better. Keywords: plastic products, defects, quality, Six Sigma